Kapitalisme Ekstraktif sebagai Manifestasi Ideologi Antroposentris dalam Novel Perempuan yang Menunggu di Lorong Menuju Laut Karya Dian Purnomo: Kajian Ekokritik - Mira Maslakhatul Latifah; Suseno Suseno (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
The exploitation of natural resources in coastal areas and small islands in Indonesia shows the strong influence of the ideology of extractive capitalism. This ideology often causes ecological conflicts. For example, in the case of the rejection of gold mining that occurred on Sangihe Island, North Sulawesi. This article examines the contemporary Indonesian novel Perempuan yang Tunggu di Lorong Menuju Laut by Dian Purnomo in representing this problem. This study is a qualitative study with an interdisciplinary approach. The main theoretical framework used is ecocriticism (Glotfelty & Buell), extractive capitalism (Gudynas, Harvey, and Bebbington), and the concept of slow violence (Nixon) with a close reading method of the text. The results of the study show that the novel represents: the ideology of anthropocentric-extractive capitalism that reduces Sangihe Island to an economic commodity; dismantles the mechanism of power that conquers law and politics through the practice of elite and ruler collusion; displays the ecocentric resistance of the Sangihe community based on ancestral wisdom and spirituality. In conclusion, this novel voices an ideological critique of the hegemony of anthropocentrism and extractive capitalism and calls for a just and sustainable ecological awareness. Given the novel's limited data, further studies could consider exploring other research subjects or developing a theory of this research subject.